Introduction of Modern Trends in City Traffic Police (CTP) Rawalpindi: A Role of Personality Leadership - Mehr, Adnan (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
Chief Traffic Officer (CTO) is an important leader and head of traffic management in five major cities of Punjab, Pakistan. The main responsibilities of CTO are guiding and directing their subordinates, supervising their work, solving problems, facilitating communication among team members, and motivating them to perform well. A valuable Chief Traffic Officers must have effective communication, strong leadership abilities, good interpersonal skills for building relationships, analytical skills for examining traffic data, and adaptability to handle changing situations. The benefits of effective leadership for Traffic Police are significant. It can lead to improved traffic flow, reduced congestion, and lower accident risks. Leadership also enhances safety by promoting best practices among team members. Strong leadership increases operational efficiency, reduces response times, and encourages better decision-making among subordinates. Furthermore, Chief Traffic Officers can build trust and a positive image within the community, resulting in better relations with the public. Chief Traffic Officers are vital leaders who ensure efficient traffic management and safety by displaying strong leadership skills and fostering a positive work environment. The present study highlights the performance of first lady Chief Traffic Officer (CTO) Rawalpindi as a leader, because the topic has been selected in view of the significance of introducing modern trends in city traffic police Rawalpindi. In this paper an attempt has been made to explore the changes in traffic police Punjab with special reference to Rawalpindi district. The researcher has deep knowledge of the study, both qualitative and quantitative methods were used.